Protagonismo surdo: currículo como construção da autoria - Ruzza, Mara Lopes Figueira de (2020)
The research addresses Deaf Protagonism and Deaf Authorship related to the process of Emancipation of the Deaf Subject, considering the Curriculum as elementary in Culture, Language and Epistemology recognition of Deaf Community. The main goal is to analyze social-educational-political contexts and narratives of Deaf Subjects, in order to recognize Deaf Protagonism as a premise for the construction of Deaf Authorship. The specific goals are to define concepts that pertain to the Deafhood, discuss the Curriculum conception, present narratives, authors and Deaf researchers and contribute with intervention proposals to guarantee Deaf Community rights. The theoretical subsidies embrace contributions from Antonio Chizzotti, Boaventura de Sousa Santos, Carlos Skliar, Enrique Dussel, José Gimeno Sacristán, Karin Strobel, Michael Whitman Apple, Oliver Wolf Sacks, Paulo Freire e Ronice Müller de Quadros, among other authors. A qualitative methodological approach was performed through bibliographic and documentary research, interviews, analysis and discussion of obtained data, revealing that the contexts in which the Deaf Subjects are inserted, and the Curriculum too, offer few situations of legitimation of linguistic, cultural and epistemological differences. as potentialities. Therefore, this research presents proposals to constitute Deaf Protagonism as a form to empower, emancipate and guarantee Deaf Authorship in social, political and educational spheres